“I Desire to Have an HIV‐Free Baby”: Pregnant and Breastfeeding Mothers’ Perceptions of Viral Load Testing and Suppression in HIV Care in Southwestern Uganda. - Kabami, Jane; Akatukwasa, Cecilia; Kabageni, Stella; Nangendo, Joanita; Byamukama, Ambrose; Atwiine, Fredrick; Mftumukiza, Valence; Tamu, Munezero John Bosco; Arinaitwe, Elizabeth; Mutabazi, Andrew; Ssebutinde, Peter; Musoke, Phillipa; et al. (Kabale University, 2024)
Introduction Viral suppression is a critical component for preventing mother-to-child transmission of HIV(MTCT). Mothers’ perceptions of viral load suppression is crucial in the attainment of successful outcomes in preventing mother-to-child transmission of HIV. We therefore aimed to explore the experiences and perceptions of women on viral suppression. Methods This was a qualitative sub-study embedded in a cluster-randomized trial (NCT04122144) designed to improve viral load outcomes among pregnant and breastfeeding mothers living with HIV in four level III/IV health facilities in Southwestern Uganda. Thirty-two in-depth interviews were conducted with pregnant and breastfeeding women with HIV from 1st March 2020 to 30th September 2020 to explore their understanding and interpretation of viral suppression. Interviews were audio-recorded, transcribed, and coded in Dedoose software for analysis. Results A total of 32 Women living with HIV were enrolled in this qualitative study. WLHIV explained viral suppression in the context of attaining good health and having HIV-free babies. Adherence to ART was presented as a key avenue to viral suppression. The level of engagement with providers was presented as a key attribute of attaining viral suppression. The participants narrated their experiences with viral load testing within the routine services. However, they revealed experiencing some proximate barriers to suppression, including anticipated stigma, challenges with nondisclosure of HIV status, pregnancy distress, and distance to the health facility. Conclusion The understanding and interpretation of viral suppression among pregnant and breastfeeding mothers living with HIV provides a basis for adopting behaviors leading to the prevention of vertical transmission of HIV. Health care workers can support women by providing clear and culturally appropriate education about viral suppression, adherence strategies and creating a supportive and non-judgmental environment.